Dynamics of Utah's agricultural landscapes in response to urbanization: A comparison between irrigated and non-irrigated agricultural lands. (April 2019) - Li, Enjie; Endter-Wada, Joanna; Li, Shujuan
Abstract: In the literature on how urbanization affects agricultural landscapes, little attention has been focused on differentiating and comparing the changes in irrigated agricultural landscapes to non-irrigated agricultural landscapes. Additionally, there have been few applications of landscape metrics for understanding agricultural landscape changes. The objectives of this study were to: (1) analyze and compare the changes of both irrigated and non-irrigated agricultural lands in a rapidly growing region; (2) identify the spatial patterns and hotspots of these changes; and, (3) examine the spatial relationships between changes in agricultural landscapes and urban development. We adopted landscape metrics and gradient analysis to assess where and how agricultural landscape changes occurred in northern Utah over the past 30 years. A revised urban gradient was also developed to detect the changes of agricultural landscapes in relation to new urban development. We found that irrigated agricultural lands were more affected by urban development than non-irrigated agricultural lands, with evidence of more patches, more irregular patch shapes, and less connectivity among patches. This study contributes not only to the existing literature on the dynamics of both irrigated and non-irrigated agricultural lands in relation to urban development, but also helps fill the gap of scant applications of landscape metrics and urban gradient analysis in agricultural areas. Most importantly, such a comprehensive examination of Utah's agricultural landscapes will serve as part of the scientific foundation for informing land use policy in the region, as well as provide lessons for other places that are facing similar agricultural land conversion challenges. Highlights: Using landscape metrics detecting agricultural landscape changes. Differentiating landscape changes of irrigated and non-irrigated agricultural lands. Irrigated agricultural landscape fragmentation under urbanization.